Evaluation method of satellite navigation signal-in-space user range error - Ershen WANG; Qing ZHANG; Hong LEI; Tao PANG (Dianxin kexue)
Signal-in-space（SIS）accuracy is one of the basic performance of satellite navigation system, and the user range error（URE）of satellite is often used as the important indicator of SIS accuracy. Based on the orbit error and clock error, the SIS URE evaluation methods of GPS and BDS were discussed. And the SIS performance of GPS and BDS were evaluated by using the measured data. The results show that all the SIS URE of GPS satellites are better than 2.2 m. In addition, except GEO-01 and GEO-04, the SIS URE of other BeiDou satellites are better than 2.5 m. And it conforms the indicators of GPS standard positioning service performance standard （GPS SPS PS, 2008）and BDS open service performance standard（BDS OS PS, 1.0）.